Interest of Chest CT to Assess the Prognosis of SARS-CoV-2 Pneumonia: An In-Hospital-Based Experience in Sub-Saharan Africa - Obe -A- Ndzem Holenn, Serge Emmanuel; Mazoba, Tacite Kpanya; Mukanga, Désiré Yaya; Zokere, Tyna Bongosepe; Lungela, Djo; Makulo, Jean-Robert; Ahuka, Steve; Mbongo, Angèle Tanzia; Molua, Antoine Aundu (Pulmonary Medicine, 2024)
Background and Objectives. The chest computed tomography (chest CT) has played an important role in the management of COVID-19. Few data on its use in sub-Saharan Africa (SSA) are reported. The objectives of this study conducted in Kinshasa, DR Congo, were to describe the lung lesions on day 1 of hospitalization in patients admitted for suspected COVID-19 and to identify those that were most associated with SARS-CoV-2 infection/RT-PCR and the determinants of chest CT associated with death. Methods. We included all patients with respiratory symptoms (dyspnea, fever, and cough) and/or respiratory failure admitted to the SOS Médecins de nuit SARL hospital, DR Congo, during the 2nd and 3rd waves of the COVID-19 pandemic. The diagnosis of COVID-19 was established based on RT-PCR anti-SARS-CoV-2 tests (G1 (RT-PCR positive) vs. G2 (RT-PCR negative)), and all patients had a chest CT on the day of admission. We retrieved the digital files of patients, precisely the clinical, biological, and chest CT parameters of the day of admission as well as the vital outcome (survival or death). Chest CT were read by a very high-definition console using Advantage Windows software and exported to the hospital network using the RadiAnt DICOM viewer. To determine the threshold for the percentage of lung lesions associated with all-cause mortality, we used ROC curves. Factors associated with death, including chest CT parameters, were investigated using logistic regression analysis. Results. The study included 200 patients (average age 56.2±15.2 years; 19% diabetics and 4.5% obese), and COVID-19 was confirmed among 56% of them (G1). Chest CT showed that ground glass (72.3 vs. 39.8%), crazy paving (69.6 vs. 17.0%), and consolidation (83.9 vs. 22.7%), with bilateral and peripheral locations (68.8 vs. 30.7%), were more frequent in G1 vs. G2 (p<0.001). No case of pulmonary embolism and fibrosis had been documented. The lung lesions affecting 30% of the parenchyma were informative in predicting death (area under the ROC curve at 0.705, p=0.017). In multivariate analysis, a percentage of lesions affecting 50% of the lung parenchyma increased the risk of dying by 7.194 (1.656-31.250). Conclusion. The chest CT demonstrated certain characteristic lesions more frequently in patients in whom the diagnosis of COVID-19 was confirmed. The extent of lesions affecting at least half of the lung parenchyma from the first day of admission to hospital increases the risk of death by a factor of 7.